SOCIALIZATION OF THE USE OF GOOGLE DRIVE AT PUSKESMAS AMBACANG KOTA PADANG - Kamal, Syamsul; Mardi, Yuli; Claudia Mareti, Windy (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Computer technology has developed significantly, from Windows application programs to increasingly sophisticated data storage media. In the past, we usually stored data using diskettes with small storage sizes, then Flashdisk and Hardisk appeared, until the entry of a new era, namely Cloud storage technology. Cloud technology itself has broad functions, one of which is as an online data storage medium. Like the familiar cloud-based data storage service, Google Drive can store up to 15GB of data for free. In addition to data storage like Google Drive, there is also cloud data storage, such as DropBox, OneDrive, and others. By using Google Drive, users experience many benefits, including being able to share data with those who need data. There is no need to store files on a flash disk or hard disk, where our files are directly stored on Google servers, which can be used at any time, modified. In using Google Drive, many Ambacang Health Center staff do not understand Google Drive. The purpose of holding this Community Service is so that all staff can understand Google Drive how to use it and its features, the results achieved are that all participants understand and understand the use of Google Drive. This socialization has been carried out 2 times, on May 27 and June 17, 2023, with lecture and discussion methods.